Market reforms in Russia: Problems and prospects - Simon György Jr. (Međunarodni Problemi, 2004)
The author analyses the economic reforms that have been implemented in Russia since 1991. In his opinion initial attempts to introduce market reforms by applying the shock therapy and forced-pace privatisation of state-owned enterprises caused high political and social costs to the Russia’s fragile democracy. Therefore the radical reform policy was temporarily suspended while the transition to a market economy was proceeded inconsistently and often unevenly. After the acute financial crisis took place in August 1998 the reform policy has been given new impetus. In the last few years substantial progress has been made in the process of privatisation implementation of reforms in the financial sphere, energy sector, in the approach to the agriculture, in the employment policy, in making changes of the tax and pension systems. All these changes contributed to attaining the sustainable economic growth. The author concludes that for the persisting crisis in a number of areas, the future of the Russian market reforms still remains largely uncertain.